Enhancing relevance and authenticity in school science: design of two prototypical activities within the FEDORA project - De Zuani Cassina, Francesco; D’Orto, Emma; Tasquier, Giulia; Fantini, Paola; Levrini, Olivia (Frontiers in Education, 2023)
We live in a historical period that sociologists call the “society of acceleration” (Rosa, 2009), where changes, mainly triggered by science and technology, occur over increasingly shorter time intervals. International reports by the OECD, the European Commission, and UNESCO highlight a worrying detachment between scientific education at school and societal issues, in terms of topics and practices. To address this gap, the H2020 project FEDORA (https://www.fedora-project.eu/) designed and implemented several school activities centred around topics related to current challenges, aimed to increase students’ feeling of relevance towards formal scientific education. These implementations are: i) based on the three FEDORA framework’s theoretical pillars: interdisciplinarity, search for new languages, future-oriented education; ii) informed by some FEDORA’s recommendations to curricula developers, then turned into operational design principles: cross and integrate different disciplines, elicit epistemic emotions, embrace and embed complexity and uncertainty, dismantle dichotomous thinking and telling, exercise scenario building and thinking about the future in a pluralistic way. After presenting the general framework and the recommendations, we will discuss the details of two activities (“Mocku for change”, “Physics of clouds”) which respectively exploit the use of creative writing and mockumentary as forms of new languages. They concern topics such as sustainability or complexity and are aimed to help students engage and make sense of contemporary challenges in a personal and emotional way. In the end, we will argue why we consider them to be examples of practical and (to some extent) reproducible activities in class, which could reduce the gap between science at school and science outside school; in this sense, we claim to shed light on possible ways by which formal educational systems can reposition themselves to deal with societal needs.